A STUDY OF RELATIONSHIP AMONG TRAITS OF PERSONALITY AND LEARNING STYLES PREFERENCES OF STUDENTS AT HIGHER EDUCATION - Akbar, Hina; Khanam, Afifa (International Journal of Psychosocial Rehabilitation, 2020)
The present study was designed to identify the relationship among traits of personality and learning styles’ preferences of students at Higher Education. All students of Higher Education of government sector Universities in Province Punjab were the population of the study. The random sampling technique was used to select 1000 students from the target population. Two standardized instruments were administered to measure the traits of personality and learning styles of the participants. The personality traits were measured by (NEO-BFI) inventory by (Costa & McCrae, 2010) having 44-items and learning styles were measured by (LSI) inventory by (Kolb & Kolb 2005) consisting 10 factors. The data were analyzed by applying Pearson correlation coefficient to investigate the relationship between styles of learning and their personality traits while the prediction study was conducted through regression analysis. The results of the study showed that converging style of learning is a significant predictor of Neuroticism, whereas the assimilating style of learning is significant predictor of Extraversion and Conscientiousness. The accommodating style of learning is also significant predictor of Neuroticism and Conscientiousness. There was found a significant relationship between agreeableness (trait of personality) and styles of learning (assimilating, accommodating and diverging). The study holds implications for accommodating students with different traits of personality and styles of learning in the classroom.